Behaviour of mercury during Co-incineration of sewage sludge and municipal solid waste. (20th April 2020) - Sun, Yunan; Chen, Guanyi; Yan, Beibei; Cheng, Zhanjun; Ma, Wenchao
Abstract: Co-incineration is promising for disposal of sewage sludge (SS) and municipal solid waste (MSW) with energy recovery, although mercury (Hg) emission in this process is non-negligible. In this work, a series of experimental and simulation works was conducted to provide knowledge about the distribution, ecological toxicity, and transformation of Hg during co-incineration of SS and MSW. The experimental results show that co-incineration can increase the Hg content in incineration ash and reduce the amount of Hg released into the atmosphere. The optimal blending ratio for Hg enrichment was 54 wt% SS and 46 wt% MSW. A modified three-step sequential extraction method was used to investigate the chemical species of Hg in incineration ash. It was found that when SS accounted for 50 wt% ∼75 wt% of the feedstock, the direct toxicity risk of Hg in incineration ash was reduced because of the presence of less hazardous chemical forms of Hg. Thermodynamic equilibrium simulation was also conducted on incineration flue gas. The results show that co-incineration caused more gaseous Hg 0 to be oxidized to Hg 2+ during the cooling process, leading to less environmental risk to the atmosphere. It is hoped that this work can help develop better co-incineration strategies and guide downstream Hg control technology, to dispose of and recover energy from SS and MSW with a cleaner approach. Graphical abstract: Image 1 Highlights: Behaviour of Hg during co-incineration of sewage sludge and municipal solid waste. Co-incineration makes more Hg in ash and less in atmosphere. Co-incineration reduces direct ecological toxicity risk of Hg in ash. Co-incineration rises potential ecological toxicity risk of Hg in ash. Cl concentration affects Hg 0 oxidization during flue gas cooling process.